1992
DOI: 10.1111/j.1365-2044.1992.tb02005.x
|View full text |Cite
|
Sign up to set email alerts
|

Late postoperative nocturnal dips in oxygen saturation in patients undergoing major abdominal vascular surgery

Abstract: SummaryTwenty-four patients (23 male) who presented for aortic reconstructive surgery were studied with pulse oximetry on a pre-operative night and during the first five postoperative nights. Patients with five or more dips in oxygen saturation of greater than 4% (with a prompt recovery back toward baseline of 3% or more) per hour of monitoring were classified as having a significant abnormality of respiration. Pre-operatively, four of 24 patients ( I 7%) demonstrated such an abnormality. Postoperatively. 12pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…OSA patients are known to have a higher incidence of difficult intubation, 18 postoperative complications, 1920 increased intensive care unit admissions, 7 and greater duration of hospital stay. 21 Memtsoudis and colleagues 9 found that OSA was associated with a significantly higher incidence of pulmonary complications.…”
Section: Discussionmentioning
confidence: 99%
“…OSA patients are known to have a higher incidence of difficult intubation, 18 postoperative complications, 1920 increased intensive care unit admissions, 7 and greater duration of hospital stay. 21 Memtsoudis and colleagues 9 found that OSA was associated with a significantly higher incidence of pulmonary complications.…”
Section: Discussionmentioning
confidence: 99%
“…18 A high incidence of early and late postoperative nocturnal hypoxemic episodes in healthy patients undergoing surgery has been reported in a number of studies. [19][20][21] However, the currently available literature on the occurrence of perioperative respiratory complications among surgical patients with OSA is too limited to make any major correlations. The objective of this study was to test the hypothesis that OSA is a risk factor for the development of postoperative complications.…”
Section: Résumémentioning
confidence: 99%
“…Therefore, alternative screening tools have been tested to assess for the severity of sleep-disordered breathing preoperatively. In their study using preoperative overnight oximetry in 24 patients, Reeder et al [10, Class II]. demonstrated “significant abnormalities of respiration” (SARs) postoperatively in all patients with preoperative SARs.…”
Section: Introductionmentioning
confidence: 99%